Improve critical thinking skills through the virtual field trip learning media at Clungup Mangrove Conservation - Hidayatullah, Ilham Adenan; Sahrina, Alfi; Almira, Nikita Jasmine (Jurnal Praksis dan Dedikasi Sosial, 2025)
This study aims to improve critical thinking skills through the development of Virtual Field Trip (VFT) learning media in the Clungup Mangrove Conservation. Critical thinking skills are essential in education, especially in understanding complex environmental issues. This research explores the use of VFT technology to enhance these skills in the context of environmental conservation education. This research utilizes a type of development research or Research and Development (R&D). The development model used in this research is ADDIE (Analyze, Design, Development, Implementation, Evaluation). The research combined qualitative and quantitative data collected through expert validation and student responses. questionnaires and interviews were conducted to collect detailed feedback. The validation results showed high scores, with an average score of 94.11% from the experts, indicating that the VFT media is highly suitable for educational purposes. Feedback from students showed an approval rate of 89.22%, indicating the effectiveness of this media in delivering conservation materials and improving critical thinking skills. The difference of the research is that VFT will be developed with the aim of improving students' critical thinking skills, besides that the advantage of this research lies in the content provided, the content is created using various shooting angles, including from cameras and drones, to provide a richer and more comprehensive point of view, also the learning video in this research also features CMC managers, to provide a deeper insight into the conservation practices carried out. This study concludes that VFT can be a valuable tool in geography education, especially for conservation topics.